APLIKASI TIGA DIMENSI VIRTUAL DENGAN MENGGUNAKAN 5DT DATA GLOVE 5 ULTRA - Yulia Yulia; Rudy Adipranata; Wiradinata Eddy (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2008)
One of active area in information technology research is development of virtual reality (VR). It is a technology which can simulate real world activities in a virtual world. Virtual reality consists of software and hardware which is usually in the form of device that captures human movement. Then VR sends signal of that movement to computer. The signal will be received and processed and shown on the screen, so that the movement can be simulated. In this research, we develop an application that can receive hand movement input with 5DT Data Glove 5 Ultra and create natural and accurate hand movement animation output for hand opening closing and other gestures. Experiments show that there are some gestures though have different physical shapes but are recognized as the same gestures because of sensor limitation in data glove. Keywords: data glove, animation, virtual reality